2014
DOI: 10.2337/db13-1032
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein PTB and MicroRNA-221 Coregulate AdipoR1 Translation and Adiponectin Signaling

Abstract: Adiponectin receptor 1 (AdipoR1) mediates adiponectin's pleiotropic effects in muscle and liver and plays an important role in the regulation of insulin resistance and diabetes. Here, we demonstrate a pivotal role for microRNA-221 (miR-221) and the RNA-binding protein polypyrimidine tract-binding protein (PTB) in posttranscriptional regulation of AdipoR1 during muscle differentiation and in obesity. RNA-immunoprecipitation and luciferase reporter assays illustrated that both PTB and miR-221 bind AdipoR1-39UTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Interestingly, a recent report characterized a developmentally regulated alternate splice variant of AdipoR1 in human subjects that was strongly enhanced during skeletal muscle differentiation and was decreased in diabetic patients, and the protein level of AdipoR1 accurately represented these changes but not total mRNA levels that accounted for all AdipoR1 splice variants (34). Our data gains further support from another recent report, which describes that microRNA-221 and the RNA binding protein polypyrimidine tract binding protein regulate AdipoR1 protein expression and are induced in genetic and diet-induced mouse models of obesity (35).…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, a recent report characterized a developmentally regulated alternate splice variant of AdipoR1 in human subjects that was strongly enhanced during skeletal muscle differentiation and was decreased in diabetic patients, and the protein level of AdipoR1 accurately represented these changes but not total mRNA levels that accounted for all AdipoR1 splice variants (34). Our data gains further support from another recent report, which describes that microRNA-221 and the RNA binding protein polypyrimidine tract binding protein regulate AdipoR1 protein expression and are induced in genetic and diet-induced mouse models of obesity (35).…”
Section: Discussionsupporting
confidence: 78%
“…To decipher intact AdipoR1 expression in bones from its depletion in db skeletal muscle, we assessed microRNA-221 (miR-221) and RNA binding protein polypyrimidine tract binding protein (PTB) levels because they negatively regulate AdipoR1 expression (49). miR-221 level in bone and muscle across all ages was significantly higher in both diabetic strains than wt, although compared with bone, differences in muscle was higher (two-to threefold in bone vs. three-to sixfold in muscle) (Fig.…”
Section: Bones Of Insulin-resistant Mice Express Functional Adipor1mentioning
confidence: 99%
“…Thus, it is also possible that hnRNPI may regulate the expression of proteins that alter IRAK1 protein turnover. Of note, hnRNPI is capable of modulating the activity of microRNAs in disease pathogenesis and many important biological processes [30,3942]. It has been reported that miR-146a controls both translation and degradation of epithelial IRAK1 in the neonatal intestine [19].…”
Section: Discussionmentioning
confidence: 99%